Characterization of physicochemical properties of fermented soybean curd residue by Morchella esculenta. (April 2016) - Li, Shuhong; Chen, Ye; Li, Kejuan; Lei, Zhongfang; Zhang, Zhenya
Abstract: Soybean curd residue is a relatively abundant and inexpensive food waste. In this study, it was reused as fermentation substrate for Morchella esculenta ( M. esculenta ). To evaluate the reutilization potential, the physicochemical properties of fermented soybean curd residue (FSCR) were investigated and compared to the unfermented soybean curd residue (USCR). In detail, physical characteristics include morphology, hygroscopicity, thermostability and color. Chemical characteristics were represented by proximate composition, free amino acids, polysaccharides, total polyphenol, pH, and titratable acidity. The obtained samples were characterized by scanning electron microscope (SEM), thermogravimetry (TG), differential thermal analysis (DTA) and fourier transform infrared (FTIR). Experimental results indicated that the FSCR shows a higher thermostability, porous and homogeneous structure. In addition, the nutritional contents of FSCR significantly increased compared with USCR, such as free amino acids (from 2343.32 ± 2.43 to 5060.25 ± 3.80 nmol/g), polysaccharides (from 25.22 ± 2.23 to 95.82 ± 1.37 mg/g) and total polyphenol (from 5.99 ± 0.27 to 7.70 ± 0.18 mg/g). This study suggested that fermentation by M. esculenta can be an effective approach to increase the utilization potential of soybean curd residue. Highlights: Morchella esculenta was used to ferment soybean curd residue (SCR). Physicochemical properties of fermented SCR were systematically evaluated. Free amino acids, polysaccharides and total polyphenol obviously increased by fermentation. Morphology, hygroscopicity, thermostability and color of fermented SCR were studied.